Condition Monitoring of a Small Four-stroke Petrol Engine using Vibration Signals - Klinchaeam, Songpon; Nivesrangsan*, Pornchai; Lokitsangthong, Ming (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
This paper concerns with condition monitoring method of a small, four-stroke, petrol engine using vibration signal based on time domain and crank angle domain analysis techniques. Acquired vibration signals on the engine can be used to study engine processes and abnormal conditions inm the engine cycle such as intake/exhaust valve operations, ignition process, combustion process, etc. In this study, vibration signals were used to study mechanical and fluid flow processes in the engine cycle. Vibration signals were applied to monitor abnormal conditions of intake/exhaust valve clearances and spark plug gap and also can be possible to develop to monitor more complex small to large petrol engines. Keywords: condition monitoring, vibration signals, fault condition, intake/exhaust valveclearances and spark plug gap * Corresponding author: Tel: 02-988-3666 ext.3110 Fax: 02-988-3666 ext.3106 E-mail: nporncha@mut.ac.th